Initial inpatient management of adolescents and young adults admitted with severe malnutrition due to anorexia nervosa: protocol for a systematic review - Stéphanie Proulx-Cabana; Danielle Taddeo; Olivier Jamoulle; Jean-Yves Frappier; Fannie Tremblay-Racine; Chantal Stheneur (Journal of Eating Disorders, 2021)
Abstract Background Anorexia Nervosa (AN) is a highly prevalent disease in adolescents and young adults (AYAs). The quality of initial inpatient medical management in a patient with severe malnutrition due to AN is crucial to prevent further medical instability. This review aims to inventory evidence regarding initial refeeding and management of AYAs with AN in an inpatient setting, in order to avoid medical complications. Methods A systematic review will be conducted using PubMed, MEDLINE, All EBM Reviews, Embase, PsycINFO, Cochrane Database and CINAHL. The search strategy consists of terms related to anorexia, hospitalization and Pediatrics. Randomized controlled trials, case-control studies, cross-sectional and cohort studies will be included. Participants will include adolescents and adults 18–24 years old diagnosed with AN and meeting criteria for severe disease. The primary outcome will be any of the following complications: hypophosphatemia, refeeding syndrome, hypoglycemia, cardiac arrythmia, hepatic cytolysis or death. Data will be extracted and the risk of bias will be assessed by one author and reviewed by a second author. Results will be presented in a systematic narrative synthesis format. The quality of evidence for all outcomes will be evaluated using the GRADE methodology. Discussion This systematic review will examine current evidence on initial inpatient refeeding and help to document effectiveness of initial inpatient management in AYAs with severe AN in avoiding further medical complications. Trial registration This study is registered on PROSPERO under the reference number CRD42019123608 .